“Os alemães ultramarinos também estão ajudando”: o trabalho do Comitê Alemão de Socorro às Vítimas de Guerra de Porto Alegre (1940-1943) (Revista de História Regional, 2025)
This study is guided by the humanitarian aid provided by organizations based in Brazil to German civilians and prisoners of war during World War II. As a case study, it analyzes the work of the German Committee for War Victims Relief, headquartered in Rio de Janeiro, through its German Subcommittee, based in Porto Alegre, Rio Grande do Sul, between 1940 and 1943, both operating under the Brazilian Red Cross. A microhistorical analysis allows for the examination of these organizations’ networked operations, their credibility based on the volume of donations collected, and the role of beneficence as a social status within both the national society and ethnic communities. Therefore, this study highlights the role played by these humanitarian organizations—both local and international—in the broader context of humanitarian aid during World War II. This research contributes to a deeper understanding of the connections between humanitarian organizations operating in Brazil and the global dynamics of the 1940s.
Keywords: Brazilian Red Cross; German Committee for War Victims Relief; Humanitarian aid; Rio Grande do Sul; World War II